2018
DOI: 10.1590/1806-90882018000200010
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF IRRIGATION, PLANTATION DENSITY AND clonal composition ON WOODY BIOMASS QUALITY FOR BIOENERGY IN A SHORT ROTATION CULTURE SYSTEM WITH WILLOWS (Salix spp.)

Abstract: A short rotation intensive system with willows was analyzed with the following aims: a - to determine the effects of irrigation, genotype and plantation density on wood anatomy, wood density, moisture content, lower heating value, total ash content and energy accumulated in the woody biomass; b - to explore the relationships between anatomical and physical wood properties and the parameters determining their quality as a biofuel. A complete factorial experiment was set up, with three factors and two levels for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Also Stolarski et al (2011) did not show significant differences between the planting densities, and the moisture content ranged from 47.5% to 52.0%. Achinelli et al (2018) found a trend to higher moisture content with a lower planting density. Many studies have shown that the water content in willow stems depends on the genotype (Szczukowski et al 2005, Stolarski et al 2011, Achinelli et al 2018.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Also Stolarski et al (2011) did not show significant differences between the planting densities, and the moisture content ranged from 47.5% to 52.0%. Achinelli et al (2018) found a trend to higher moisture content with a lower planting density. Many studies have shown that the water content in willow stems depends on the genotype (Szczukowski et al 2005, Stolarski et al 2011, Achinelli et al 2018.…”
Section: Resultsmentioning
confidence: 89%
“…Achinelli et al (2018) found a trend to higher moisture content with a lower planting density. Many studies have shown that the water content in willow stems depends on the genotype (Szczukowski et al 2005, Stolarski et al 2011, Achinelli et al 2018. Moreover, in the present research, a significant variation of this parameter between willow cultivars was observed.…”
Section: Resultsmentioning
confidence: 89%
“…At the end of D r a f t 7 the experiment, the total above ground dry weight (leaves plus stem, TDW) was determined after drying them to constant weight at 65°C. The basic wood density (BWD) was determined on a 10 cm subsample obtained from the basal part of the stem by fluid displacement as described in Achinelli et al (2018). Before the beginning of the treatment, the latest expanded leaf was tagged with a colored wire.…”
Section: Flooding Experiments Descriptionmentioning
confidence: 99%
“…This means the soil influences biomass chemical composition. Similarly, Achinelli et al [25] showed that irrigation has a statistically significant impact on the higher heating value ( HHV ) of biomass (willows). On the other hand, irrigation did not have an impact on ash content, vessel diameter, fiber wall area, and fiber wall thickness [25].…”
Section: Introductionmentioning
confidence: 99%